Ignition and combustion of high-energy materials containing aluminum, boron and aluminum diboride; MATEC Web of Conferences; Vol. 194 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2018) - Korotkikh A. G. Aleksandr Gennadievich (Les Ulis, EDP Sciences, 2018)
Title screen